Case report: Lingering post-concussive symptoms in a pediatric patient with presumed Ehlers-Danlos syndrome - Curry, Tala Maris; Esfandiarei, Mitra; Thomas, Theresa Currier; Rastogi, Reena Gogia (Frontiers in Pediatrics, 2022)
Background Connective tissue disorders such as Ehlers-Danlos Syndrome (EDS) can affect collagen and elastin content and structure, including weakening of tissues and vasculature, thus contributing to multiple systemic manifestations. Prior research has successfully focused on peripheral life-threatening manifestations resulting in increased life expectancy, yet clinical observations have warranted investigation of neurological vulnerability, where little is known. Compromised brain tissues and cerebrovasculature could leave these patients vulnerable to mild traumatic brain injury (TBI), with increased severity and duration of post-concussive symptoms and delayed recovery. Clinical reports in adults indicate that higher severity of symptoms after a mild TBI, such as a concussion, can unmask connective tissues disorders leading toward diagnosis. This clinical case report is an example of a pediatric patient with presumed Ehlers-Danlos syndrome who demonstrates increased vulnerability to mild TBI/concussion. Patient A pediatric female patient presents with unexplained lingering post-concussive symptoms, including trouble sleeping, nausea, frontal headaches, dizziness, visual changes, fatigue, and left-sided weakness more than 6 months post-mild concussion. Patient history of hypermobility, joint derangement, soft tissue mobility, and bruising suggests a potential diagnosis of Ehlers-Danlos syndrome, which may explain symptom severity and length of recovery. Discussion This case is the first documented instance of increased vulnerability to TBI in a pediatric patient with presumed Ehlers-Danlos syndrome. It highlights the need for awareness and prevention of injury in this vulnerable patient population, suggests more targeted therapeutic intervention for recovery, and demonstrates the need for preclinical research evaluating the influence of genetic mutations associated with connective tissue disorders on the central nervous system.